An Alternative Way to Make Knowledge Sharing Work in Online Communities? The Effects of Hidden Knowledge Facilitators. (3rd January 2019) - Li-Ying, Jason; Zhang, Zhinan; Long, Qing
ABSTRACT: Some firms use hidden knowledge facilitators (HKFs) to facilitate knowledge sharing among employees within intrafirm online communities. These firms hope for enhanced knowledge sharing outcomes within their organizations without letting employees know that HKFs exist. Yet, the extent to which HKFs' interventions are effective remains unknown to researchers and managers. Built on the knowledge sharing (KS) literature, this study explores the unique roles of HKFs as moderators between a company and its employees. We develop several hypotheses to test the impact of the quantity and quality of HKFs' online interventions on several KS outcomes. By analyzing log data of a Chinese corporation's online R&D community, we find that (1) the quantity of HKFs' intervention has a mostly positive impact on KS outcomes; (2) the quality of HKFs' intervention has a mixed impact on several KS outcomes, depending on which aspect of quantity is considered; and (3) the quality of HKFs' intervention also moderates the positive impact of the quantity of HKFs' intervention in different ways on different intended KS outcomes. This study makes a clear contribution to the literature on knowledge sharing and knowledge facilitation by demonstrating the impact of HKFs on KS outcomes in a Chinese context.